The Highlighted Life: The Humanistic Orientation of War Narration in Chinese Children’s Films of the New Period - Tan, Fengxia; Li, Lu (SARE: Southeast Asian Review of English, 2018)
Compared with earlier works in the genre, the narration of war in Chinese children’s films of the New Period (post1978) demonstrates a trend of transformation from political to humanistic orientation, which is closely related to the revival of humanism. Moving away from the traditional hero narrative, the creators of Chinese children’s war films have developed growth narratives that emphasise the complexity of human nature, cruel narratives of reflection, and playful narratives which make use of laughter and irony — all of which can be seen to be modes within the humanistic convention. These narratives re-examine the meaning of war and revolution, reflect deeply on the relationship between war and the fate of children, closely observe human feelings and human nature in war situations, and highlight the individual’s life against the backdrop of the course of history. Involving experimentation and innovation, such narratives of war of the New Period point to a deeper and more diversified development in Chinese children’s films, which though they provide a unique window into lives affected by war also hold up a mirror that reflects a global understanding of war and peace.